Respuestas

2012-10-16T23:12:25+02:00

x + y = 5 ( un numero mas otro da 5 )  x - y = 1 (el 1° numero menos el s2° da 1)

 

y= 5 - x      -------------->                   x - (5 - x) = 1

                                                       x - 5 + x = 1

                                                       x + x = 1 + 5

                                                           2x = 6

                                                            x = 6 : 2

y = 5 - x               <--------------               x = 3

y = 5 - 3

y = 2

 

Saludoss..